Magnetic cores, magnetic components and electronic devices

By using soft magnetic particle materials of specific sizes and ratios in the magnetic core, the problem of insufficient anti-voltage characteristics under high relative permeability in the prior art is solved, and better anti-voltage performance is achieved.

JP7649142B2Active Publication Date: 2025-03-19TDK CORP
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2021003703
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-03-23
Filing Date
2021-01-13
Publication Date
2025-03-19
Estimated Expiration
2041-01-13

AI Technical Summary

Technical Problem

It is difficult for existing magnetic cores to simultaneously improve the voltage resistance characteristics when they have high relative permeability.

Method used

A soft magnetic particle material with large and small particles has Heywood diameters of 5 μm to 25 μm and 0.5 μm to 3 μm, respectively, and the voltage resistance characteristics of the magnetic core are improved by adjusting the average longitudinal ratios A1 and A2 of the particles.

Benefits of technology

While maintaining high relative permeability, the voltage resistance of the magnetic core is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007649142000012
    Figure 0007649142000012
  • Figure 0007649142000013
    Figure 0007649142000013
  • Figure 0007649142000001
    Figure 0007649142000001
Patent Text Reader

Abstract

To obtain a magnetic core or the like which is improved in relative permeability and withstand voltage characteristics.SOLUTION: On a cross-sectional surface, a magnetic core includes; a large particle observed as a soft magnetic having a Heywood diameter of 5 μm or more and 25 μm or less; and a small particle observed as the soft magnetic particle having a Heywood diameter of 0.5 μm or more and 3 μm or less. When an average aspect ratio of large particles is A1, and the average aspect ratio of small particles is A2, 1.00≤A1≤1.50, 1.30≤A2≤2.50 and A1<A2 are satisfied.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a magnetic core, a magnetic component, and an electronic device. [Background technology]

[0002] Patent Document 1 describes an inductor in which a dust core obtained by compressing a metal magnetic powder and a coil are integrally molded. However, when using a metal magnetic powder, the core loss is likely to be large. Here, the core loss can be improved by using an amorphous alloy powder as the metal magnetic powder. However, in this case, it is known that it becomes difficult to improve the density of the dust core during molding.

[0003] Patent Documents 2 and 3 propose using a mixture of crystalline alloy magnetic powder and amorphous alloy magnetic powder.

[0004] Patent Document 4 describes that by using an amorphous soft magnetic powder having a high average practical sphericity, it is possible to provide an inductor or the like having lower loss than before. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2003-309024 A [Patent Document 2] JP 2004-197218 A [Patent Document 3] JP 2004-363466 A [Patent Document 4] Patent No. 5110660 Summary of the Invention [Problem to be solved by the invention]

[0006] An object of the present invention is to obtain a magnetic core or the like having improved voltage resistance characteristics while maintaining a high relative magnetic permeability. [Means for solving the problem]

[0007] In order to achieve the above object, the magnetic core according to the present invention comprises: In a cross section, the large particles are observed as soft magnetic particles having a Heywood diameter of 5 μm or more and 25 μm or less, and the small particles are observed as soft magnetic particles having a Heywood diameter of 0.5 μm or more and 3 μm or less, The average aspect ratio of the large particles is A1, and the average aspect ratio of the small particles is A2, 1.00≦A1≦1.50 1.30≦A2≦2.50 A1 <A2 Meet the following.

[0008] The magnetic core of the present invention uses large and small particles having a specific average aspect ratio, and the average aspect ratio of the small particles is set to be equal to the average aspect ratio of the large particles. twist They discovered that by increasing the thickness, it is possible to improve the voltage resistance characteristics while maintaining a high relative permeability.

[0009] In the cross section, the maximum value of the Heywood diameter of the soft magnetic particles other than the large particles and the small particles may be 40 μm or less.

[0010] The large particles may have an average ellipticity of 0.93 or more in their cross sections.

[0011] The large particles may comprise nanocrystals.

[0012] The small particles may contain Fe as a main component.

[0013] The small particles may contain, as main components, Fe and at least one selected from Si and Ni.

[0014] The magnetic component of the present invention includes the above-mentioned magnetic core.

[0015] The electronic device of the present invention includes the above magnetic core. [Brief description of the drawings]

[0016] [Figure 1] This is an example of a chart obtained by X-ray crystal structure analysis. [Diagram 2] 2 is an example of a pattern obtained by profile fitting the chart of FIG. 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] Hereinafter, an embodiment of the present invention will be described.

[0018] The magnetic core according to this embodiment includes, in cross section, large particles observed as soft magnetic particles having a Heywood diameter of 5 μm or more and 25 μm or less, and small particles observed as soft magnetic particles having a Heywood diameter of 0.5 μm or more and 3 μm or less.

[0019] The total area ratio of the large particles to the entire cross section may be 10% or more, or may be 30% or more. The total area ratio of the small particles may be 10% or more, or may be 15% or more. In addition, the total area ratio of the large particles may be S1 and the total area ratio of the small particles may be S2, and S1:S2 may be 1:9 to 9:1.

[0020] The Heywood diameter is the diameter of a circle equivalent to a projected area. The Heywood diameter of the soft magnetic particle in this embodiment is expressed as (4S / π) where S is the area of ​​the soft magnetic particle in the cross section. 1 / 2 It is.

[0021] In the magnetic core according to this embodiment, the average aspect ratio of the large particles is A1, the average aspect ratio of the small particles is A2, and 1.00≦A1≦1.50 1.30≦A2≦2.50 A1 <A2 It is a magnetic core that satisfies the above.

[0022] Furthermore, the large particles and small particles according to this embodiment may have a coating on the surface. The coating may be an insulating coating. There is no particular limitation on the type of coating, and any coating formed by a coating commonly used in this technical field may be used. Examples of the coating include iron oxides, phosphates, silicates (water glass), soda-lime glass, borosilicate glass, lead glass, aluminosilicate glass, borate glass, and sulfate glass. Examples of phosphates include magnesium phosphate, calcium phosphate, zinc phosphate, manganese phosphate, phosphorus phosphate, and the like. Acid Examples of silicates include sodium silicate. There is no particular limit to the thickness of the coating. If the coating is formed on a large particle, it may be 5 nm or more and 100 nm or less on average. If the coating is formed on a small particle, it may be 5 nm or more and 100 nm or less on average. Note that the thickness of the coating is significantly smaller than the particle diameter of each particle, so it does not substantially affect the Heywood diameter and aspect ratio of each particle.

[0023] The magnetic core according to the present embodiment may also have a resin used as a binder. There is no particular limit to the type of resin. Examples include silicone resin and epoxy resin. There is also no particular limit to the amount of resin contained in the magnetic core. For example, the amount may be 1.5 parts by mass or more and 5.0 parts by mass or less per 100 parts by mass of the soft magnetic particles.

[0024] A method for observing the cross section of the magnetic core will be described below.

[0025] First, the magnetic core is cut and the cross section obtained is polished to prepare an observation surface, which is then observed with a SEM and an SEM image is taken.

[0026] There is no particular limit to the size of the observation range by SEM, and it is sufficient that any large particle can be observed in 100 or more, preferably 1000 or more. Alternatively, different observation ranges may be set and SEM images of each observation range may be taken, and the above number of particles may be observed in the total of the multiple SEM images.

[0027] There is no particular limit to the magnification of the SEM image, as long as it allows the measurement of various parameters according to the present embodiment. For example, it may be 200 times or more and 5000 times or less.

[0028] The aspect ratio of each soft magnetic particle is calculated by dividing the length of the major axis by the length of the minor axis.

[0029] In the magnetic core according to the present embodiment, since the average aspect ratio A1 of the large particles, the average aspect ratio A2 of the small particles, and the relationship between A1 and A2 are all as described above, it is possible to improve the voltage resistance characteristics while maintaining the relative permeability. Note that A2-A1 may be ≧0.01.

[0030] The reasons why the relative permeability and voltage resistance characteristics of the magnetic core according to this embodiment are improved will be described below.

[0031] The voltage endurance characteristics of a magnetic core are more likely to be improved when the soft magnetic particles contained in the magnetic core are in surface contact than when they are in point contact. When comparing surface contact with point contact with the soft magnetic particles, the contact area between the soft magnetic particles is larger in the surface contact case. Here, the larger the contact area between the soft magnetic particles, the greater the voltage application. Canada In other words, when the contact between the soft magnetic particles is surface contact, the voltage applied per unit area of ​​the contact becomes smaller. Canada When the soft magnetic particles are in contact with each other, there are fewer locations where the electric field concentrates. As a result, when the contact between the soft magnetic particles is surface contact, the voltage resistance of the magnetic core is improved. Also, the greater the degree to which the soft magnetic particles contained in the magnetic core are deformed from a spherical shape, the more likely it is that the contact between the soft magnetic particles will be surface contact. In other words, it is believed that the greater the aspect ratio of the soft magnetic particles, the more likely it is that the voltage resistance of the magnetic core will improve.

[0032] However, at the same time, if the aspect ratio of the soft magnetic particles is too large, the electric field tends to concentrate in the long axis direction of the soft magnetic particles when a voltage is applied. The concentration of the electric field reduces the voltage resistance of the magnetic core. Therefore, simply increasing the aspect ratio of all the soft magnetic particles is unlikely to improve the voltage resistance of the magnetic core, and in some cases it may even reduce it.

[0033] The inventors have found that the phenomenon that the larger the aspect ratio of the soft magnetic particles, the lower the voltage endurance characteristics of the magnetic core is, is likely to occur in soft magnetic particles with a large particle diameter. They have also found that the voltage endurance characteristics are improved by deforming the small particles more than the large particles to increase the aspect ratio of the small particles. The details of why the voltage endurance characteristics are improved by increasing the aspect ratio of the small particles are unclear. However, when the aspect ratio of the small particles is increased to increase the proportion of surface contact, it is believed that the number of places where the electric field concentrates when a voltage is applied, especially in the large particles, is reduced compared to the case where the aspect ratio of the large particles is increased to increase the proportion of surface contact. It is believed that the reduction in the number of places where the electric field concentrates in the large particles suppresses the deterioration of the voltage endurance characteristics.

[0034] Furthermore, generally, increasing the filling rate of soft magnetic particles tends to increase the relative permeability. However, increasing the filling rate of soft magnetic particles narrows the spacing between the soft magnetic particles. Therefore, increasing the filling rate of soft magnetic particles increases the number of locations where the electric field is concentrated when a voltage is applied. For these reasons, generally, increasing the filling rate of soft magnetic particles deteriorates the voltage resistance characteristics.

[0035] In other words, in the past, the relative permeability was improved by improving the filling rate, but improving the filling rate deteriorates the withstand voltage characteristics, making it difficult to improve the withstand voltage characteristics when the relative permeability is high. The present inventors have succeeded in improving the withstand voltage characteristics when the relative permeability is high by setting both the aspect ratio of the large particles and the aspect ratio of the small particles within a specific range and further making the aspect ratio of the small particles larger than the aspect ratio of the large particles.

[0036] There is no particular limit to the method of calculating the packing rate of the magnetic core. For example, the above observation surface is observed using a SEM. Then, the area ratio of the particles to the entire area of ​​the observation surface is calculated. In this embodiment, the area ratio and the packing rate are considered to be equal, and the area ratio is set as the packing rate.

[0037] In the cross section, the maximum Heywood diameter of the soft magnetic particles that do not fall into the category of the large particles or the small particles may be 40 μm or less. In other words, the Heywood diameter of the soft magnetic particle having the largest Heywood diameter in the cross section may be 40 μm or less.

[0038] The Heywood diameter of the soft magnetic particle having the largest Heywood diameter in the cross section may be 25 μm or less, that is, soft magnetic particles having a larger Heywood diameter than the large particles may not be observed in the cross section.

[0039] When the maximum value of the Heywood diameter of the soft magnetic particles other than the large particles and the small particles exceeds 40 μm, it becomes difficult to improve the voltage resistance characteristics of the magnetic core. This is because when soft magnetic particles with a large Heywood diameter are contained in the magnetic core, there are portions where the number of particles per unit length in the voltage application direction decreases. In particular, when resin is filled between the particles, the difference in voltage resistance characteristics depending on whether or not soft magnetic particles with a large Heywood diameter are contained tends to be large.

[0040] The large particles may have an average ellipticity in cross section of 0.930 or more, more preferably 0.950 or more.

[0041] To evaluate the particle shape, 2 × (π × cross-sectional area) 1 / 2 Although the circularity calculated by the formula (4×cross-sectional area / (long axis×short axis×π) is often used, in this embodiment, the particle shape is evaluated by the elliptical circularity, which is calculated by the formula (4×cross-sectional area / (long axis×short axis×π).

[0042] In general, when a particle is flat, the circularity is low. However, even when a particle is flat, the elliptical circularity is high. On the other hand, even when a particle has a concave or distorted shape, the circularity may not be low. However, when a particle has a concave or distorted shape, the elliptical circularity is low. In addition, when a particle has a shape with large irregularities, both the circularity and the elliptical circularity are low. That is, in order to evaluate whether a particle is deformed other than flat when viewed from a perfect circle, for example, whether a particle has a concave, a distortion, or an irregularity, it may be preferable to use the elliptical circularity.

[0043] Here, whether the large particles contained in the magnetic core are flattened or not does not affect the voltage resistance. On the other hand, whether the large particles are deformed other than flattened or not, for example, whether the large particles contained in the magnetic core are recessed or distorted, or whether they have large irregularities or not, is likely to affect the voltage resistance. This is because the voltage resistance of the magnetic core is improved as the number of places where the electric field is concentrated when voltage is applied is reduced, and the number of places where the electric field is concentrated is less dependent on whether the large particles are flattened or not, and is more dependent on whether the large particles are deformed other than flattened or not.

[0044] There is no particular restriction on the microstructure inside the soft magnetic particles. For example, the soft magnetic particles may have a structure including amorphous or may have a structure made of crystals. It is preferable that the large particles have a nano-hetero structure containing initial microcrystals with an average crystal grain size of 0.3 nm to 10 nm in the amorphous. When the soft magnetic particles have a structure made only of amorphous or a nano-hetero structure, the amorphization rate X described later is 85% or more. When the soft magnetic particles have a structure made of crystals, the amorphization rate X described later is less than 85%. When the filling rate is approximately the same, when the large particles have a nano-hetero structure, the relative permeability is improved compared to when the large particles have a structure made only of amorphous. Furthermore, it is preferable that the large particles have a structure made of crystals, an average crystal grain size is 1 nm to 30 nm, and a maximum crystal grain size is 100 nm or less (nano-crystalline structure). When the filling rate is approximately the same, when the large particles have a nano-crystalline structure, the relative permeability of the magnetic core is further improved. In addition, in soft magnetic particles containing crystals, especially nanocrystals, it is normal for a single particle to contain many crystals. In other words, the particle size of the soft magnetic particles is different from the crystal grain size. There is no particular limit to the method of calculating the crystal grain size. For example, there is a method of calculating the crystal grain size by analyzing the half-width by XRD measurement and evaluating the crystallite size, and a method of calculating the crystal grain size by observing the crystals using a TEM.

[0045] When the soft magnetic particles have an amorphous structure, the soft magnetic particles are, for example, represented by the composition formula (Fe (1-(α+β)) X1 α X2 β ) (1-(a+b+c+d+e+f)) M a B b P c S d C e S f It may have a main component consisting of X1 is one or more selected from the group consisting of Co and Ni; X2 is one or more selected from the group consisting of Al, Mn, Ag, Zn, Sn, As, Sb, Cu, Cr, Bi, N, O and rare earth elements; M is one or more selected from the group consisting of Nb, Hf, Zr, Ta, Mo, W, Ti and V; 0≦a≦0.14 0≦b≦0.20 0≦c≦0.20 0≦d≦0.14 0≦e≦0.20 0≦f≦0.02 0.70≦1-(a+b+c+d+e+f)≦0.93 α ≧ 0 β ≧ 0 0≦α+β≦0.50 The above composition formula is expressed by the atomic ratio.

[0046] Furthermore, the nanocrystals contained in the soft magnetic particles (particularly large particles) may be Fe-based nanocrystals. Fe-based nanocrystals are crystals whose average crystal grain size is on the nano-order (specifically, 0.1 nm or more and 100 nm or less) and whose Fe crystal structure is bcc (body-centered cubic lattice structure). There is no particular limit to the method of calculating the average crystal grain size of Fe-based nanocrystals. For example, there is a method of calculating the crystal grain size by analyzing the half-width by XRD measurement and evaluating the crystallite size, and a method of calculating the crystal grain size by observing using a TEM. There is also no particular limit to the method of confirming that the crystal structure is bcc. For example, there is a method of confirming using XRD and a method of confirming by analyzing the electron beam diffraction pattern obtained using a TEM.

[0047] In this embodiment, the Fe-based nanocrystals may have an average crystal grain size of 1 to 30 nm. Such soft magnetic particles having a structure made of Fe-based nanocrystals tend to have a high saturation magnetic flux density and a low coercive force. That is, the soft magnetic properties are easily improved. That is, by including the soft magnetic particles, the magnetic core is easily made to have a low coercive force and a high relative permeability. Furthermore, the saturation magnetic flux density of the magnetic core containing the soft magnetic particles increases, and the DC superposition properties of the magnetic core are improved. As described above, by using soft magnetic particles having a structure made of Fe-based nanocrystals, the properties of the magnetic core are easily improved.

[0048] When the soft magnetic particles have a structure made of Fe-based nanocrystals, the soft magnetic particles may have a composition formula of, for example, (Fe (1-(α+β)) X1 α X2 β ) (1-(a+b+c+d+e+f)) M a B b P c S d C e S f It may have a main component consisting of X1 is one or more selected from the group consisting of Co and Ni; X2 is one or more selected from the group consisting of Al, Mn, Ag, Zn, Sn, As, Sb, Cu, Cr, Bi, N, O and rare earth elements; M is one or more selected from the group consisting of Nb, Hf, Zr, Ta, Mo, W, Ti and V; 0≦a≦0.14 0≦b≦0.20 0≦c≦0.20 0≦d≦0.14 0≦e≦0.20 0≦f≦0.02 0.70≦1-(a+b+c+d+e+f)≦0.93 α ≧ 0 β ≧ 0 0≦α+β≦0.50 The above composition formula is expressed by the atomic ratio.

[0049] In the manufacturing method of the magnetic core described later, when the soft magnetic metal powder containing the soft magnetic particles having the above composition is heat treated, Fe-based nanocrystals are easily precipitated in the soft magnetic particles. soft magnetic particles It is easy to use this as the starting material for soft magnetic metal powder having soft magnetic particles in which Fe-based nanocrystals are precipitated.

[0050] When Fe-based nanocrystals are precipitated in soft magnetic particles by heat treatment, the soft magnetic particles before heat treatment may have a structure consisting of only amorphous material, or may have a nanoheterostructure in which primary microcrystals exist in the amorphous material. The primary microcrystals may have an average crystal grain size of 0.3 nm or more and 10 nm or less. In addition, when the soft magnetic particles have a structure consisting of only amorphous material or a nanoheterostructure, the amorphization rate X described later is 85% or more.

[0051] The small particles preferably contain Fe as a main component, and more preferably contain Fe and at least one selected from Si and Ni as a main component.

[0052] Incidentally, containing Fe as a main component means that the Fe content in the entire soft magnetic particle is 85 at % or more and 100 at % or less.

[0053] "Containing Fe and at least one selected from Si and Ni as the main components" means that the soft magnetic particles contain at least Fe and at least one selected from Si and Ni, and the total content of Fe, Si and Ni in the entire soft magnetic particle is 85 at% or more and 100 at% or less. In this case, the Fe content may be 15 at% or more and 95 at% or less. The total content of Si and Ni may be 3 at% or more and 90 at% or less. There are no particular limitations on the type of elements other than the main components. Examples include Co, Cr, Al, etc.

[0054] By having the small particles have the above composition, it is possible to produce a magnetic core with high magnetic properties. That is, when the magnetic core has small particles containing Fe as a main component, it is possible to increase the saturation magnetic flux density of the small particles. Therefore, it is possible to improve the saturation magnetic flux density of the entire magnetic core, and it is possible to improve the DC superposition characteristics of the magnetic core. Also, when the magnetic core has small particles containing Fe and at least one selected from Si and Ni as a main component, it is possible to increase the relative permeability of the small particles. Therefore, it is possible to improve the relative permeability of the entire magnetic core.

[0055] A method for manufacturing the magnetic core according to this embodiment will be described below, but the method for manufacturing the magnetic core is not limited to the method described below.

[0056] First, a soft magnetic metal powder containing the soft magnetic particles according to the present embodiment is prepared. The soft magnetic metal powder according to the present embodiment can be obtained by mixing a soft magnetic metal powder that will eventually become mostly large particles and a soft magnetic metal powder that will eventually become mostly small particles.

[0057] The soft magnetic metal powder, the majority of which will ultimately be large particles, can be produced by, for example, a gas atomization method.

[0058] In the gas atomization method, the raw metal is melted and the molten metal is powdered using the gas atomization method to produce soft magnetic metal powder. The composition of the molten metal is the same as that of the large particles to be ultimately obtained. At this time, the molten metal is dripped from a container with an outlet toward a cooling section. The temperature of the molten metal is the spray temperature. There is no particular limit to the spray temperature. For example, it is between 1200°C and 1600°C. The higher the spray temperature, the easier it is for the average aspect ratio to approach 1, and the easier it is for the average particle size to become smaller.

[0059] In addition, a gas injection nozzle equipped with a gas injection port is arranged so as to surround the discharge port. From the gas injection port, high-pressure gas (gas with an injection pressure (gas pressure) of 2.0 MPa or more and 10 MPa or less) is injected toward the molten metal dropped from the discharge port. As a result, the molten metal becomes a large number of droplets. By controlling the pressure of the high-pressure gas at this time, it is possible to change the particle size and shape of the soft magnetic metal powder finally obtained. Specifically, when the amount of molten metal injected is the same, the higher the pressure of the high-pressure gas, the smaller the particle size of the soft magnetic metal powder finally obtained. In other words, the particle size and shape of the soft magnetic metal powder can be changed by the ratio of the pressure of the high-pressure gas to the amount of molten metal injected.

[0060] The gas to be injected from the gas injection port is preferably an inert gas such as nitrogen gas, argon gas, or helium gas, or a reducing gas such as an ammonia decomposition gas. Genus If oxidation is difficult, air may be used.

[0061] The shape of the cooling section onto which the molten metal is dripped is not particularly limited, but may be, for example, a cylinder formed with a cooling liquid flow inside to collide with the molten metal. In this case, the particle size and average aspect ratio of the large particles in the finally obtained magnetic core can be changed by controlling the injection amount of the molten metal and the water pressure of the cooling liquid flow in addition to the high-pressure gas pressure described above. In other words, the particle size and average aspect ratio of the large particles are controlled by controlling the balance between the injection amount of the molten metal, the high-pressure gas pressure, and the water pressure of the cooling liquid flow. The injection amount of the molten metal may be 0.5 kg / min or more and 4.0 kg / min or less, and the water pressure may be 5.0 MPa or more and 20.0 MPa or less. Specifically, the larger the injection amount, the larger the particle size of the large particles is likely to be. Also, the smaller the water pressure, the more likely the average aspect ratio of the large particles is likely to approach 1. In other words, when changing the aspect ratio of the particles without changing the particle size, it is necessary to appropriately adjust the injection amount, the high-pressure gas, and the water pressure of the cooling liquid flow.

[0062] The molten metal discharged into the cooling liquid flow collides with the cooling liquid flow and is further divided and refined. As the molten metal is refined, the refined molten metal changes shape as it is cooled and solidified, becoming solid soft magnetic metal powder. The soft magnetic metal powder discharged together with the cooling liquid is separated from the cooling liquid in an external storage tank or the like and taken out. There is no particular limit to the type of cooling liquid. For example, cooling water is used. If no cooling liquid is used, the soft magnetic metal powder, which will eventually become mostly large particles, is likely to contain coarse crystals with a crystal grain size exceeding 100 nm.

[0063] In addition, the shorter the time between when the molten metal is dropped and when it collides with the cooling liquid flow, the less likely the molten metal is to be oxidized, and the more likely it is to become amorphous, as the rapid cooling effect is promoted.

[0064] The obtained soft magnetic metal powder may be subjected to heat treatment. There is no particular restriction on the conditions of the heat treatment. For example, the heat treatment may be performed at 400 to 700 ° C for 0.1 to 10 hours. By performing the heat treatment, when the microstructure of the particles is a structure having only amorphous or a nanoheterostructure in which the primary crystallites are present in the amorphous, the microstructure of the particles tends to become a structure containing nanocrystals. Then, the coercive force of the soft magnetic metal powder tends to decrease. Note that, when the temperature of the heat treatment is too high, the coercive force of the soft magnetic metal powder tends to increase.

[0065] There is no particular limitation on the method for confirming the microstructure of the soft magnetic metal powder. For example, it can be confirmed by XRD. In addition, the microstructure of the soft magnetic metal powder before compaction and the microstructure of the particles contained in the magnetic core after compaction are usually the same.

[0066] In this embodiment, a soft magnetic metal powder having an amorphization rate X of 85% or more as shown in the following formula (1) has a structure consisting only of amorphous matter or a nanoheterostructure, and a soft magnetic metal powder having an amorphization rate X of less than 85% has a structure consisting of crystals. X = 100 - (Ic / (Ic + Ia) × 100) ... (1) Ic: Crystalline scattering integrated intensity Ia: Amorphous scattering integrated intensity

[0067] The amorphous ratio X is calculated by performing X-ray crystal structure analysis by XRD on the soft magnetic metal powder, identifying the phase, reading the peaks of crystallized Fe or compounds (Ic: crystalline scattering integrated intensity, Ia: amorphous scattering integrated intensity), determining the crystallization ratio from the peak intensity, and calculating the amorphous ratio X using the above formula (1). The calculation method will be described in more detail below.

[0068] The soft magnetic metal powder according to this embodiment is subjected to X-ray crystal structure analysis by XRD to obtain a chart as shown in Fig. 1. This is subjected to profile fitting using the Lorentz function of the following formula (2), and a crystalline component pattern α showing the crystalline scattering integrated intensity as shown in Fig. 2 is obtained. c , amorphous component pattern α showing amorphous scattering integral intensity a , and the combined pattern α c+a From the crystalline scattering integrated intensity and the amorphous scattering integrated intensity of the obtained pattern, the amorphization rate X is calculated by the above formula (1). The measurement range is a diffraction angle 2θ range of 30° to 60° where an amorphous-derived halo can be confirmed. In this range, the error between the integrated intensity actually measured by XRD and the integrated intensity calculated using the Lorentz function is set to within 1%.

[0069]

number

[0070] Soft magnetic metal powder, the majority of which ultimately becomes small particles, is produced by various powdering methods, such as the liquid phase method, spray pyrolysis method, and melting method.

[0071] In addition, the aspect ratio can be changed by further treating the obtained soft magnetic metal powder with a ball mill. Specifically, the soft magnetic metal powder can be deformed by the treatment with a ball mill, and the average aspect ratio of the small particles contained in the finally obtained magnetic core can be increased. The longer the treatment time with the ball mill, the more deformed the soft magnetic metal powder becomes. In addition, the average aspect ratio of the small particles contained in the finally obtained magnetic core can be controlled by mixing small particles that have been treated with a ball mill with small particles that have not been treated with the ball mill.

[0072] The average particle size of the soft magnetic metal powder, most of which will ultimately be small particles, can be controlled by appropriately removing coarse particles and / or fine particles using an air classifier.

[0073] When manufacturing a magnetic core from the soft magnetic metal powder according to the present embodiment, first, a soft magnetic metal powder that will eventually become mostly large particles and a soft magnetic metal powder that will eventually become mostly small particles are mixed. There is no particular limitation on the mixing method. The mixing ratio may be, for example, 9:1 to 1:9 in mass ratio of the soft magnetic metal powder that will eventually become mostly large particles: the soft magnetic metal powder that will eventually become mostly small particles.

[0074] Next, resin may be further added to the mixed soft magnetic metal powder as necessary. The ratio of resin to the entire magnetic core may be set to 1.5 mass% or more and 5.0 mass% or less. Furthermore, the powder mixed with the resin may be granulated.

[0075] The powder thus obtained is then filled into a mold and compressed to obtain a magnetic core. There are no particular restrictions on the conditions for compression molding. For example, compression molding can be performed at 1 t / cm 2 More than 8t / cm 2 The molding may be performed at the following molding pressure: The filling rate can be controlled by changing the molding pressure.

[0076] Although the magnetic core according to the present embodiment has been described above, the magnetic core of the present invention is not limited to the above embodiment.

[0077] There is also no particular limitation on the applications of the magnetic core of the present invention. For example, coil components (magnetic components) such as inductors, choke coils, and transformers can be mentioned. Furthermore, electronic devices using the magnetic core of the present invention, such as DC-DC converters, can be mentioned. EXAMPLES

[0078] The present invention will be described below with reference to more detailed examples, but the present invention is not limited to these examples.

[0079] Experimental Example 1 For samples No. 1 to 28, soft magnetic metal powders that ultimately consisted of large particles were produced by gas atomization. The composition was Fe 0.800 Nb 0.070 B 0.098 P 0.030 S 0.002 It was decided.

[0080] At this time, the amount of molten metal sprayed, the temperature of the molten metal (spray temperature), the spray gas pressure, and the water pressure of the cooling liquid flow were set to the values ​​shown in Table 2, and soft magnetic metal powders were produced in which the average aspect ratios A1 of the large particles in the final magnetic core were 1.01, 1.30, 1.50, and 2.00. The gas type used was Ar. Other conditions were also appropriately controlled so that the average particle diameter (D50) of the obtained soft magnetic metal powder on a number basis was 10.3 μm.

[0081] The obtained soft magnetic metal powder was then subjected to a heat treatment at 600° C. for 1 hour in an Ar atmosphere.

[0082] The average particle size (D50) of the obtained soft magnetic metal powder based on the number was confirmed to be 10.3 μm. The average particle size based on the number was measured using Morphologi G3. In addition, it was confirmed using XRD and STEM that each soft magnetic metal powder had a nanocrystalline structure. In addition, after preparing a magnetic core using the obtained soft magnetic metal powder by the method described below, the cross section of the magnetic core was observed using SEM at a size where at least 10 soft magnetic particles were observed. The observation by SEM was repeated so that a total of 100 or more soft magnetic particles were observed. Then, the Heywood diameter of 100 or more soft magnetic particles was measured. As a result, the average particle size (D50) of the soft magnetic particles in the Heywood diameter was 7.5 μm. The reason why the average particle size of the soft magnetic particles measured by observing the cross section of the magnetic core is smaller than the average particle size of the actual soft magnetic metal powder is because the soft magnetic metal powder is cut at an arbitrary location when the cross section of the magnetic core is cut.

[0083] In the samples No. 1 to 28, soft magnetic metal powders that were mostly small particles were prepared by spray pyrolysis. The composition was Fe 100 at %. In addition, the average particle diameter (D50) of the small particle powder was controlled to be 1.5 μm by appropriately removing coarse powder and / or fine powder using an air classifier. In addition, at this point, the soft magnetic metal powder has a shape close to a perfect sphere, and the average aspect ratio of the soft magnetic particles when a magnetic core is produced using this soft magnetic metal powder is 1.00. In addition, after producing a magnetic core using the obtained soft magnetic metal powder by the method described later, the cross section of the magnetic core was observed using an SEM at a size where at least 10 soft magnetic particles were observed. The observation using the SEM was repeated so that a total of 100 or more soft magnetic particles were observed. Then, the Heywood diameter of 100 or more soft magnetic particles was measured. As a result, the average particle diameter (D50) of the soft magnetic particles in the Heywood diameter was 1.1 μm.

[0084] Next, by performing processing using a ball mill, soft magnetic metal powders were produced in which the average aspect ratios A2 of the small particles in the final magnetic core were 1.00, 1.30, 1.50, 1.70, 2.00, 2.50, and 3.00. The processing times are shown in Table 3.

[0085] Then, for the soft magnetic metal powder that would eventually become mostly large particles, a coating with an average thickness of 20 nm was formed using zinc phosphate, and for the soft magnetic metal powder that would eventually become mostly small particles, a coating with an average thickness of 10 nm was formed using zinc phosphate.

[0086] Then, the soft magnetic metal powder that will eventually become mostly large particles and the soft magnetic metal powder that will eventually become mostly small particles were mixed in a mass ratio of 8:2. If the density of the powders is the same, the above mass ratio and area ratio (S1:S2) will roughly match. It is also possible to calculate the mass ratio of the large particles to the small particles from the area ratio of the large particles to the small particles and the density of each particle. Furthermore, epoxy resin was diluted with acetone and added to 100 parts by mass of the soft magnetic metal powder obtained by mixing to make 3 parts by mass. Then, the mixture was kneaded in a kneader, dried, and the resulting aggregate was sized to have an average particle diameter of 355 μm or less in the volume particle size distribution to obtain granules. This was filled into a mold. The shape of the mold was such that the shape of the magnetic core finally obtained was toroidal.

[0087] Next, the soft magnetic metal powder was pressure-molded. The molding pressure was controlled so that the packing rate of the magnetic core obtained would be the value shown in Table 1. Specifically, the molding pressure was 1 to 8 ton / cm. 2 was controlled within the range.

[0088] For each experimental example, a cross section cut parallel to the molding direction (height direction) was observed. Specifically, an SEM was used to set the observation range so that 10 or more large particles were visible. The magnification was 1000x. It was also confirmed that for each experimental example, the area ratio of large particles to all soft magnetic particles contained in the magnetic core was 10% or more, and the area ratio of small particles was 10% or more.

[0089] Then, the average aspect ratio A1 of large particles, the average ellipticity of large particles, the average aspect ratio A2 of small particles, the maximum value of the Heywood diameter of soft magnetic particles, the filling rate, the relative permeability, and the breakdown voltage characteristics in the magnetic core of each experimental example were measured. The A1, A2, the average ellipticity of large particles, the maximum value of the Heywood diameter, and the filling rate of each magnetic core were calculated from SEM images. The relative permeability was measured using an Impedance / GAIN-PHASE ANALYZER (manufactured by Yokogawa Hewlett-Packard Co., Ltd., 4194A). A case where the relative permeability was higher than 40 was regarded as good.

[0090] For the breakdown voltage characteristics of each magnetic core, a pair of In-Ga electrodes was formed on the magnetic core, the pair of In-Ga electrodes was sandwiched between a pair of copper plates, and the voltage when a current of 1 mA flowed by applying a voltage to the pair of copper plates was evaluated. In this experimental example, a case where it was 50 V / mm or more was regarded as good. The results are shown in Table 1.

[0091]

Table 1

[0092]

Table 2

[0093]

Table 3

[0094] From Table 1, in each example that satisfied all of 1.00 ≤ A1 ≤ 1.50, 1.30 ≤ A2 ≤ 2.50, and A1 < A2, the breakdown voltage characteristics were significantly improved compared with each comparative example that did not satisfy any of 1.00 ≤ A1 ≤ 1.50, 1.30 ≤ A2 ≤ 2.50, and A1 < A2. Also, the filling rate was equivalent in each example and each comparative example, and the relative permeability was good in each example.

[0095] Experimental Example 2 In Experimental Example 2, it was carried out under the same conditions as Experimental Example 1 except for the points described below. In Experimental Example 2, the gas pressure when producing soft magnetic metal powder in which most finally becomes large particles was changed. Then, the average particle diameter of the soft magnetic metal powder and the average aspect ratio A1 of the large particles in the finally obtained magnetic core were set to the values shown in Table 5, respectively. Also, by appropriately removing coarse powder and / or fine powder using an air classifier, the average particle diameter of the soft magnetic metal powder in which most finally becomes small particles was controlled to be the value shown in Table 4. Further, for each example, similar to Experimental Example 1, the area ratio of large particles to all soft magnetic particles contained in the magnetic core was 10% or more, the area ratio of small particles was 10% or more, the average ellipticity of the large particles was 0.95 or more, and it was confirmed that the soft magnetic metal powder in which most finally becomes large particles has a nanocrystalline structure.

[0096]

Table 4

[0097]

Table 5

[0098] From Table 4, even when changing the average particle diameter of the soft magnetic metal powder, each example satisfying all of 1.00 ≦ A1 ≦ 1.50, 1.30 ≦ A2 ≦ 2.50, and A1 < A2 had good withstand voltage characteristics despite having a high relative permeability. In addition, compared with Sample No. 31 in which the maximum value of the Heywood diameter of the soft magnetic particles exceeded 40 μm, other examples had even better withstand voltage characteristics.

[0099] Experimental Example 3 In Experimental Example 3, the atomization conditions were controlled by changing the atomization conditions from Experimental Example 1 for the average aspect ratio A1 and the average ellipticity of the large particles. The atomization conditions are shown in Table 7. The atomization conditions for Sample Nos. 38 to 42 are the same as those for Sample No. 9.

[0100] In addition, in Experimental Example 3, the soft magnetic metal powder that would eventually become mostly large particles was subjected to heat treatment in the same manner as in Experimental Examples 1 and 2 to produce soft magnetic metal powders having a nanocrystalline structure, and soft magnetic metal powders having an amorphous structure or a nanoheterostructure without heat treatment. When heat treatment was not performed, the average particle size (D50) based on the number of soft magnetic metal powders that would eventually become mostly large particles was 10.4 μm as evaluated by Morphologi G3.

[0101] Furthermore, in samples No. 39 and 41, the soft magnetic metal powder that eventually became mostly small particles had a composition mainly composed of Fe and Ni, that is, the atomic ratio was Ni 80 Fe 20 Soft magnetic metal powders were prepared in the same manner as in Experimental Examples 1 and 2, except that the soft magnetic metal powders in Samples Nos. 40 and 42 were mostly small particles, and the soft magnetic metal powders were mainly composed of Fe and Si and further contained Cr, that is, the atomic ratio was Fe 57.1 S 28.6 Cr 14.3 A soft magnetic metal powder was produced in the same manner as in Experimental Examples 1 and 2, except for the above.

[0102] The soft magnetic metal powders were combined appropriately to produce magnetic cores. The results are shown in Table 6.

[0103] [Table 6]

[0104] [Table 7]

[0105] Tables 6 and 7 show that the lower the average ellipticity of the large particles, the lower the withstand voltage. Furthermore, although the withstand voltage characteristics do not change significantly when the composition of the small particles is changed, when the microstructure of the large particles is a structure consisting only of amorphous matter or a nanoheterostructure, the relative permeability is lower than when it is a nanocrystalline structure.

[0106] Experimental Example 4 In Experimental Example 4, the same conditions were used for Sample No. 9, except that the amount of zinc phosphate added was changed to change the coating thickness of each particle. The results are shown in Table 8.

[0107] [Table 8]

[0108] As can be seen from Table 8, the same tendency was observed even when the coating thickness was changed. Also, as the coating thickness increased, the voltage resistance characteristics improved, but the relative permeability tended to decrease.

[0109] Experimental Example 5 In Experimental Example 5, the crystal structure of the soft magnetic metal powder, the majority of which ultimately became large particles, was changed by controlling the composition and atomization conditions. The composition and crystal structure are shown in Table 9. Specifically, the atomization conditions for Samples No. 51 to 56 were the same as those for Sample No. 1 shown in Table 2. The atomization conditions for Samples No. 57 to 62 were the same as those for Sample No. 1, except that cooling water was not sprayed. No heat treatment was performed on Samples No. 51 to 62. The other points were the same as those of Experimental Example 1. The composition of the large particles was described in terms of atomic ratio. The results are shown in Table 9.

[0110] [Table 9]

[0111] From Table 9, for each example satisfying all of 1.00 ≦ A1 ≦ 1.50, 1.30 ≦ A2 ≦ 2.50, and A1 < A2, the breakdown voltage characteristics were significantly improved compared to each comparative example not satisfying any of 1.00 ≦ A1 ≦ 1.50, 1.30 ≦ A2 ≦ 2.50, and A1 < A2. Also, the filling rate was the same for each example and each comparative example, and the relative permeability was good for each example. In addition, for examples where the fine structure of the large particles consisted only of amorphous (Sample Nos. 52 to 55), and for examples where the fine structure of the large particles was a crystalline structure containing coarse crystals with a crystal grain size exceeding 100 nm (Sample Nos. 58 to 61), the relative permeability was lower compared to examples where the fine structure of the large particles was a nanocrystalline structure (Sample Nos. 5, 13, 17, 21).

[0112] Experimental Example 6 In Experimental Example 6, for Sample Nos. 1 and 5, the mixing ratio of the soft magnetic metal powder that finally becomes mostly large particles and the soft magnetic metal powder that finally becomes mostly small particles was changed to be S1:S2 shown in Table 10. Also, different from Experimental Examples 1 to 5, the molding pressure was unified to 4 t / cm 2 This was to evaluate the change in the filling rate when S1:S2 was changed. Other points were carried out under the same conditions. The results are shown in Table 10.

[0113]

Table 10

[0114] From Table 10, compare the examples and comparative examples where S1:S2 are the same as each other. For each example satisfying all of 1.00 ≦ A1 ≦ 1.50, 1.30 ≦ A2 ≦ 2.50, and A1 < A2, the breakdown voltage characteristics were improved compared to each comparative example not satisfying any of 1.00 ≦ A1 ≦ 1.50, 1.30 ≦ A2 ≦ 2.50, and A1 < A2.

[0115] From Table 10, if the molding pressure was the same, the filling rate was higher when S1:S2 was 8:2. The relative permeability was highest when S1:S2 was 8:2. The higher the ratio of S2 to S1, the more the withstand voltage characteristics tended to improve. However, the higher the ratio of S2 to S1, the lower the filling rate and the lower the relative permeability.

[0116] For each example in Table 10, the molding pressure was 1 to 8 t / cm 2 The change in the filling rate was confirmed by changing between S1 and S2. When comparing examples produced at the same molding pressure, the filling rate and relative permeability were higher when S1:S2 was 8:2 regardless of the molding pressure. The higher the ratio of S2 to S1, the more the voltage resistance characteristics tended to improve. However, the higher the ratio of S2 to S1, the lower the filling rate and the lower the relative permeability. Therefore, it was confirmed that the filling property was best when S1:S2 was 8:2.

Claims

1. In a cross section, the large particles are observed as soft magnetic particles having a Heywood diameter of 5 μm or more and 25 μm or less, and the small particles are observed as soft magnetic particles having a Heywood diameter of 0.5 μm or more and 3 μm or less, The average aspect ratio of the large particles is A1, and the average aspect ratio of the small particles is A2, 1.00≦A1≦1.50 1.30≦A2≦2.50 A1<A2 Meet the magnetic core.

2. 2. The magnetic core according to claim 1, wherein in the cross section, the maximum value of the Heywood diameter of the soft magnetic particles other than the large particles and the small particles is 40 [mu]m or less.

3. 3. A magnetic core according to claim 1, wherein the large particles have an average ellipticity of 0.93 or more in the cross section.

4. A magnetic core according to any one of claims 1 to 3, wherein the large grains comprise nanocrystals.

5. 5. The magnetic core according to claim 1, wherein the small particles contain Fe as a main component.

6. 5. The magnetic core according to claim 1, wherein the small particles contain, as main components, Fe and at least one selected from the group consisting of Si and Ni.

7. A magnetic component comprising the magnetic core according to any one of claims 1 to 6.

8. 7. An electronic device comprising the magnetic core according to claim 1.

Citation Information

Patent Citations

  • Odakusuino jokasochi

    JP1976010660A

  • Coil encapsulating magnetic component and method of manufacturing the same

    JP2003309024A

  • Composite magnetic material, core using the same, and magnetic element

    JP2004197218A

  • Complex magnetic material and method for manufacturing inductor using the same

    JP2004363466A

  • Soft magnetic material for dust core and dust core

    JP2009252961A